Clinical Correlates of Aortic Stiffness and Wave Amplitude in Black Men and Women in the Community. Issue 21 (6th November 2018) - Tsao, Connie W.; Washington, Floyd; Musani, Solomon K.; Cooper, Leroy L.; Tripathi, Avnish; Hamburg, Naomi M.; Benjamin, Emelia J.; Vasan, Ramachandran S.; Mitchell, Gary F.; Fox, Ervin R.
Abstract : Background: Black individuals have greater risk for cardiovascular disease (CVD) than whites. Identifying CVD risk factors associated with abnormal aortic hemodynamics in blacks may optimize CVD prevention and treatment strategies. Methods and Results: Jackson Heart Study participants underwent applanation tonometry (2011–2016) with assessment of carotid‐femoral pulse wave velocity (CFPWV) and forward wave amplitude (FWA). CVD risk factors were assessed during examination 3 (2009–2012). We examined the association of risk factors with binary and continuous CFPWV and FWA in multivariable stepwise models. We evaluated for effect modification by sex to determine differential associations of risk factors with aortic hemodynamics in men and women. We examined 1322 individuals (mean age 66±11 years, 66% women). Age was strongly associated with elevated CFPWV (odds ratio, 4.76; 95% confidence interval, 3.84–5.89 [ P <0.0001]) and FWA (odds ratio, 2.30; 95% CI, 1.98–2.69 [ P <0.0001]). Men had greater odds of elevated CFPWV compared with women (odds ratio, 1.54; 95% confidence interval, 1.11–2.13 [ P =0.009]). Heart rate, mean arterial pressure, and use of antihypertensive medications were associated with elevated CFPWV and FWA (all P ≤0.02). Additionally, total/high‐density lipoprotein cholesterol and fasting glucose were associated with elevated CFPWV (both P ≤0.002) and use of diabetes mellitus medications was associated with elevated FWA ( P ≤0.0001). We observed a steeper association of age and mean arterial pressure with unfavorable aortic hemodynamics in women than men. Conclusions: In blacks in the community, differential CVD risk factors are associated with aortic stiffness and FWA. Future work may determine the impact of risk factor modification on abnormal central aortic hemodynamics and CVD outcomes.